2008
DOI: 10.1016/j.cpr.2008.02.001
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical framework for antigay aggression: Review of established and hypothesized effects within the context of the general aggression model

Abstract: Theory and research on antigay aggression has identified different motives that facilitate aggression based on sexual orientation. However, the individual and situational determinants of antigay aggression associated with these motivations have yet to be organized within a single theoretical framework. This limits researchers' ability to organize existing knowledge, link that knowledge with related aggression theory, and guide the application of new findings. To address these limitations, this article argues f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 93 publications
2
40
0
2
Order By: Relevance
“…This effect supports theoretical views that male homosexuality represents a core threat to heterosexual masculinity, and particularly men’s endorsement of an antifemininity theme within the male role (Parrott, 2008). Consistent with this literature, the present results observed a small, though non-significant, association ( β = .14).…”
Section: Discussionsupporting
confidence: 82%
“…This effect supports theoretical views that male homosexuality represents a core threat to heterosexual masculinity, and particularly men’s endorsement of an antifemininity theme within the male role (Parrott, 2008). Consistent with this literature, the present results observed a small, though non-significant, association ( β = .14).…”
Section: Discussionsupporting
confidence: 82%
“…Estimates of the indirect effects with confidence intervals were obtained using bootstrapping with 5,000 samples (Preacher & Hayes, 2004, 2008.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Consistent with this research, experimental studies have demonstrated that male sexual prejudice is positively associated with increased aggression toward gay, relative to heterosexual, men (Bernat, Calhoun, Adams, & Zeichner, 2001; Parrott, 2009; Parrott & Zeichner, 2005). Importantly, these effects are only observed when heterosexual men are first exposed to expressions of male-male intimacy (Parrott & Zeichner, 2005), presumably because this situational factor elicits aggression-promoting internal states (Parrott, 2008). Indeed, studies show that sexually prejudiced men who are exposed to male-male, relative to male-female intimacy, experience higher levels of self-reported anger and negative affect (e.g., Bernat et al, 2001; Hudepohl, Parrott, & Zeichner, 2010; Mahaffey, Bryan, & Hutchison, 2005a; 2005b) and hostile cognition (Parrott, Zeichner, & Hoover, 2006).…”
Section: Sexual Prejudice As a Determinant Of Aggression Toward Sexuamentioning
confidence: 99%
“…Indeed, research indicates that approximately 50% of sexual minority individuals experience bias-motivated aggression (Herek, 2009), and these victims suffer a greater severity of violence and experience greater detrimental personal and psychological effects than victims of other bias-motivated (Dunbar, 2006) and nonbiased assaults (Herek, Gillis, & Cogan, 1999). Despite a substantial literature that identifies risk factors and mechanisms for aggression toward sexual minorities (for reviews, see Franklin, 2000; Parrott, 2008), there exist few published studies that specifically examine the link between acute alcohol intoxication and bias-motivated aggression toward sexual minorities or any other stigmatized group (Hull & Van Treuren, 1986; Parrott & Miller, 2009). This is a significant oversight in the current literature.…”
mentioning
confidence: 99%